Comparison of herpesvirus isolates from falcons, pigeons and psittacines by restriction endonuclease analysis - Aini, I.; Shih, L.M.; Castro, A.E.; Zee, Y.C. (Wildlife Disease Association, 1993)
Field isolates of herpesviruses recovered from falcon, pigeon, and psittacine birds were compared by restriction endonuclease (RE) analysis using four separate enzymes. Pigeon and falcon herpesviruses had strikingly similar DNA cleavage patterns, while DNA cleavage pattern of virus isolates from a double-yellow headed Amazon and an African grey parrot had different genomic patterns to both the pigeon and falcon herpesviruses. These findings support the field observations that pigeon herpesvirus causes a fatal herpesviral infection in the livers of pigeon-eating falcons.